El cumplimiento de los deberes formales de los contribuyentes expendedores de ropa del sector la laguna, cantón Latacunga, provincia de Cotopaxi en el segundo semestre del año 2016 - Flores Toapanta, Vilma Verónica (2017)
At present the small traders have become an important sector for the economic contribution and the change of the productive matrix, in addition they are key in the development and dynamism of the country. This sector maintains a high economic movement and represents an important percentage for the contribution of taxes. The objective of the research was to determine the level of compliance of the formal duties of the sector's garment vending taxpayers, the Laguna Canton Latacunga, Province of Cotopaxi. During the execution of the investigation the quantitative methodology was applied, because the facts were quantified, analyzed and interpreted results, at the same time the research technique was used as the survey being this of great help because it facilitated the process of gathering of data and information….